COMPARATIVE ANALYSIS OF DIRECT WASTE USING SOFTWARE CUTTING OPTIMIZATION PRO AND THE COST OF USING CONVENTIONAL REINFORCEMENT AND WIREMESH IN FLOOR SLAB WORK. (CASE STUDY: OFFICE AND DEPOT CONSTRUCTION PROJECT OF PT. GUDANG GARAM) - Hidayah, Fitri Nur; Rafie, Rafie; Nuh, Safaruddin M.; Syahrudin, Syahrudin; Lusiana, Lusiana (Jurnal Teknik Sipil, 2023)
Rebar is one of the main materials in a building. The material has been widely innovated by product providers. In addition to using conventional reinforcement on the floor slab, it is now possible to replace the reinforcement with wire mesh reinforcement. Because material costs are a very large cost in construction projects, it is necessary to do proper material planning. This final project will compare the two reinforcements with the aim that project implementers can plan materials appropriately so that it is expected to minimize the huge cost expenditure. In this final project, the reinforcement in the floor slab work will be reviewed in terms of direct waste reinforcement which will be assisted by software cutting optimization pro and reinforcement costs using the AHSP stipulated by Permen PUPR No.1 of 2022. After various stages are carried out, a comparison of the direct waste level, direct waste cost, and cost of the two reinforcements will be obtained. A Comparison of the three reviews found that wire mesh reinforcement is more efficient than using conventional reinforcement.